2020
DOI: 10.2217/3dp-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

3D Bioprinting of Glioblastoma Model

Abstract: The most common and malignant primary brain tumor in adults is glioblastoma (GBM). In vitro 3D brain models are needed to better understand the pathological processes underlying GBM and ultimately develop more efficient antineoplastic agents. Here, we describe the bioprinting methods that have been used to fabricate volumetric GBM models. We explain several factors that should be considered for 3D bioprinting, including bioinks, cells and construct designs, in relation to GBM modeling. Although 3D-bioprinted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…There is an increasing interest in the development of 3D complex functional architectures with appropriate biomaterials and cells, in particular with the strategy of mimicking the cellular microenvironment of native tissues. Three-dimensional printing has emerged as a powerful tool for tissue engineering, which applies additive manufacturing to biofabricate 3D tissue-resembling objects with a high degree of spatial organization [1,2]. A layer-by-layer deposition of materials [1], called (bio)inks, is performed in specifically designed 3D shapes [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing interest in the development of 3D complex functional architectures with appropriate biomaterials and cells, in particular with the strategy of mimicking the cellular microenvironment of native tissues. Three-dimensional printing has emerged as a powerful tool for tissue engineering, which applies additive manufacturing to biofabricate 3D tissue-resembling objects with a high degree of spatial organization [1,2]. A layer-by-layer deposition of materials [1], called (bio)inks, is performed in specifically designed 3D shapes [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The TME of gliomas, especially that of glioblastoma multiforme (GBM), can be divided into three main components: the ECM, the surrounding cells, and the hypoxia gradient [87]. Wang et al used glioma stem cells of the GSC23 line, suspended them in an alginate/transglutaminase/fibrinogen/thrombin bioink, and subsequently printed a 3D grid-like structure [88].…”
Section: Gliomamentioning
confidence: 99%
“…ECM-based tumor models have their own constraints, such as the limited control over the tumor cell distribution within the hydrogel. Bio-printing can solve this issue under physiologically relevant conditions using a cost-effective approach with high reproducibility, which is highly desired for HTS (Parra-Cantu et al, 2020 ) ( Figure 2D ). Several studies have reported models with 3D bioprinted GBM cancer cells alone (Lee et al, 2020 ), or in co-culture with HAs, neural cells (Tang et al, 2020 ), or even macrophages (Heinrich et al, 2019 ; Tang et al, 2020 ).…”
Section: Modeling Vascularized Gbmmentioning
confidence: 99%